Chemical composition and antibacterial activity of essential oil from the leaves of Murraya koenigii (L.) Spreng. - B.Gopalakrishnan, M. Jayaraman and V. Venkatesalu, A. Senthilkumar, (Journal of Experimental Sciences, 2015)
Chemical composition and antibacterial activity of the leaf essential oil of Murraya koenigii were investigated against clinically isolated bacterial strains. Fourteen compounds were identified by GC and GC-MS accounting for about 98.1% of the total essential oil. a-pinene (49.3%), 2H-1-benzopyran (24.3%), 2-allyl-4-methylphenol (16.7%) and D-isomenthol (2.1%) were identified as the major chemical compounds. The essential oil produced mean zone of inhibition ranged between 14.0 and 7.6 mm. The essential oil showed antibacterial activity against all the bacterial strains tested with the MIC values of 125-500 Âµg/ml. Although, the activity of the essential oil against the clinical isolates were much less than of Ciprofloxacin, the standard drug used, the demonstrated antibacterial activities of M. koenigii leaf essential may support the folkloric uses of the plant.Â 